Drywood Termite, Cryptotermes cavifrons Banks (Insecta: Isoptera: Kalotermitidae) - Angela S. Brammer; Rudolf H. Scheffrahn (EDIS, 2004)
Termites of the genus Cryptotermes were sometimes called powderpost termites because of the telltale heaps of fecal pellets (frass) that accumulate beneath infested wood. Fecal pellets of Cryptotermes, however, are similar in size and shape to other comparably sized species of Kalotermitidae. All are now collectively known as drywood termites. The most economically significant termite in this genus, Cryptotermes brevis (Walker), commonly infests structures and was at one time known as the “furniture termite,” thanks to the frequency with which colonies were found in pieces of furniture. A member of the same genus that might be mistaken for C. brevis upon a first, cursory examination is C. cavifrons, a species endemic to Florida. This document is EENY-279, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2002.